Human CAR Gene Expression in Nonpermissive Hamster Cells Boosts Entry of Type 12 Adenovirions and Nuclear Import of Viral DNA - Hochstein, Norbert (American Society for Microbiology (ASM), 2008)
Adenovirus type 12 (Ad12) propagation in hamster BHK21 cells is blocked prior to viral DNA replication. The amounts of Ad12 DNA in the nuclei or cytoplasm of hamster cells are about 2 orders of magnitude (2 h postinfection [p.i.]) and 4 to 5 orders of magnitude (48 h p.i.) lower than in permissive human cells. Cell line BHK21-hCAR is transgenic for and expresses the human coxsackie- and adenovirus receptor (hCAR) gene. Nuclear uptake of Ad12 DNA in BHK21-hCAR cells is markedly increased compared to that in naïve BHK21 cells. Ad12 elicits a cytopathic effect in BHK21-hCAR cells but not in BHK21 cells. Quantitative PCR or [(3)H]thymidine labeling followed by zone velocity sedimentation fails to detect Ad12 DNA replication in BHK21 or BHK21-hCAR cells. Newly assembled Ad12 virions cannot be detected. Thus, the block in Ad12 DNA replication in hamster cells is not released by enhanced nuclear import of Ad12 DNA.